From Financial to Moral-Ethical Concerns: Changing Pattern of Divorce Reasons at the Religious Court of Bekasi, Indonesia - Mazro'atus Sa'adah; Mudzhar, M. Atho’; Abdullah, Abdul Gani; Subhan, Zaitunah (Islamic Family Law Department, Sharia and Law Faculty, UIN Sunan Ampel Surabaya, Indonesia, 2024)
This study examines the changing causes of divorce at the Religious Court of Bekasi between 2011 and 2020. Employing a qualitative approach, the study utilizes descriptive analysis of recorded divorce cases to explore these trends. The findings reveal fluctuations in the primary causes of divorce. Initially, economic factors dominated, but over time, moral and ethical issues, such as infidelity, domestic violence, and neglect of responsibilities, became more prominent. Subsequently, economic reasons reemerged as a leading factor, albeit with a smaller margin. Social issues such as ineffective communication, lack of mutual respect, and external family interference also contribute to divorce cases. These changes are influenced by the evolving social dynamics and modernity of Bekasi's urban society, where perceptions of family roles have transitioned from a primarily economic partnership to one emphasizing love, self-fulfillment, and emotional connection. This study highlights that social transformation and modernity significantly impact divorce patterns in Bekasi, with economic and moral-ethical factors alternately taking precedence over the past decade.